Information and Communication Technology As Media Innovation and Sources of Learning in School - Dwi Amelia Galuh Primasari; Suparmanto Suparmanto; M Imansyah (Universitas Bengkulu, 2019)
The influence of the development of information and communication technology encourages innovation in learning activities. This study aims to describe the use of ICT as a medium and source of learning in schools. The research was conducted in 3 locations, namely Public Elementary School 2 Gelumbang and Public Elementary School 29 Gelumbang, Gelumbang District, and Senior Scondary School 1 Sungai Rotan, Sungai Rotan District, Muara Enim Regency, South Sumatra Province. This study uses a qualitative-descriptive approach, with observation techniques, and interviews. The results of the study concluded: (1) the teacher invites students to use ICT facilities in schools in learning activities; (2) the use of ICT-based resources and learning media in schools, among others, using computers, laptops, LCD (Liquid Crystal Display), smartphones, internet networks, and Microsoft office applications; (3) to improve teacher competence in utilizing ICT, teachers need to continue to familiarize themselves. Besides that, there should be a solution to the barriers to the use of ICTs, including conducting training through teacher working group activities (TWG), in order to support the improvement of teachers' abilities and knowledge in the ICT field.